2011
DOI: 10.1111/j.1365-313x.2011.04584.x
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of cytokinin signalling in Arabidopsis thaliana is mediated by differing ligand affinities and expression profiles of the receptors

Abstract: SUMMARYArabidopsis thaliana has three membrane-located cytokinin receptors (AHK2, AHK3 and CRE1/AHK4), which are sensor histidine kinases containing a ligand-binding CHASE domain. Despite their structural similarity the role of these receptors differs in planta. Here we have explored which parameters contribute to signal specification. In a bacterial assay, the CHASE domain of AHK2 has a similar ligand binding spectrum as CRE1/ AHK4. It shows the highest affinity for isopentenyladenine (iP) and trans-zeatin (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
163
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 54 publications
(89 reference statements)
13
163
1
2
Order By: Relevance
“…Based on studies with Arabidopsis, cZ has generally been thought to be a cytokinin derivative with no or low activity (Inoue et al, 2001;Spíchal et al, 2004;Romanov et al, 2006;Stolz et al, 2011). Although recent studies with nonmodel plants suggested possible roles for cZ (Vyroubalová et al, 2009;Goggin et al, 2010;Lomin et al, 2011), its physiological significance was yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies with Arabidopsis, cZ has generally been thought to be a cytokinin derivative with no or low activity (Inoue et al, 2001;Spíchal et al, 2004;Romanov et al, 2006;Stolz et al, 2011). Although recent studies with nonmodel plants suggested possible roles for cZ (Vyroubalová et al, 2009;Goggin et al, 2010;Lomin et al, 2011), its physiological significance was yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, contrary to widespread assumptions, cZ plays a role as an active cytokinin in several aspects of rice growth and development. Previous biochemical studies on HK cytokinin receptors showed that the affinity to cZ was similar to that to tZ in maize HK (ZmHK1; Lomin et al, 2011), while cZ affinities were much lower than tZ affinities in Arabidopsis HKs (AHK2, AHK3, and CRE1/AHK4; Romanov et al, 2006;Stolz et al, 2011). Four cytokinin receptors have been identified in rice (OsHK3, OsHK4, OsHK5, and OsHK6; Ito and Kurata, 2006;Pareek et al, 2006;Du et al, 2007;Schaller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Individual receptors of Arabidopsis thaliana are most sensitive to the bases of the isoprenoid-type CKs and thidiazuron, but differ in their recognition of CK metabolites. In contrast to CRE1/AHK4 and AHK2, which effectively discriminate between CK basis and their conjugates, AHK3 has broader specificity and, alongside ciszeatin and dihydrozeatin (DZ) (Spíchal et al 2004;Stolz et al 2011) noticeably recognises CK ribosides and nucleotides (Spíchal et al 2004). AHK3 shows a stronger preference towards trans-zeatin-type CKs than iP-type CKs, whereas CRE1/AHK4 recognises both trans-zeatin and iP similarly (Spíchal et al 2004;Romanov et al 2006).…”
Section: Ck Perception and Signal Transductionmentioning
confidence: 99%
“…Based on the opposite predominant occurrences of trans-zeatin-and iP-type CKs in xylem and phloem sap, respectively, and the fact that AHK3 is predominantly expressed in the shoot but CRE1/AHK4 is expressed in the root (Ueguchi et al 2001b;Higuchi et al 2004), the specific function of AHK3 of responding to a longdistance signal coming from the roots was suggested (Romanov et al 2006). A recent study by Stolz et al (2011) showed that AHK2 is highly similar to CRE1/AHK4 in ligand preference and function, as proved by the promoter-swap experiments. Interestingly, in contrast to AHKs, all maize His kinases have very high affinity to both isoprenoid and aromatic CKs and are effectively activated by cis-zeatin (Yonekura- .…”
Section: Ck Perception and Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation